An unusual cause of dysphagia: a vascular ring. - Hall, R. J. (BMJ Group, 1994)
A 40 year old woman presented with dysphagia which was due to one of the forms of vascular ring. Her symptoms were relieved by relatively conservative surgery. The means of diagnosis and the surgical approach are discussed.